Support of smoking restriction in public areas among adolescents in Malaysia-the findings from tobacco and e-cigarette survey among adolescents in Malaysia (TECMA) - Lim, Kuang Hock; Heng, Pei Pei; Lim, Hui Li; Cheong, Yoon Ling; Chee, Cheong Kee; Sumarni Mohd Ghazali,; Lim, Jia Hui (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Adolescents are the future generation, and their support for smoke-free policies might create momentum for future stringent smoke-free initiatives. This study aimed to determine the levels and factors associated with support for smoking in public areas among Malaysian school-going adolescents aged 10-19 years. The data were derived from the Tobacco and E-cigarettes among adolescents in Malaysia (TECMA), which employed the cross-sectional study design and multistage sampling to select the representative samples of school-going adolescents. Data was obtained through self-administered of pre-validated questionnaire. Descriptive study, cross-tabulation and multivariable analysis were used for analysis. Majority of respondents supported smoking restriction in public areas (86.3%, 95 CI 85.4-87.1). The proportion and likelihood of support of smoke-free initiative were higher among respondents with better knowledge of the harmful effects of second-hand smoke (SHS), been taught in school about the health effects of smoking, older age group (16-19 years), female, those students schooling in urban areas, Malay and other Bumiputras from Sabah and Sarawak. However, current smokers and ECV users were less likely to support smoke-free initiatives in public areas. The level of support for smoke-free initiative in public areas was high among youths in Malaysia, and this might offer promising prospects to expand the non-smoking areas to more public areas in the future.